Implications of breast cancer healthcare policies and practices on palliative care utilization in Albania over the last decade - Pampuri, Orjola; Zotaj, Henrik (Intelektual Pustaka Media Utama, 2025)
Palliative care improves the quality of life for patients with severe diseases like breast cancer. The objective of this study was to describe the variation of age of breast cancer patients (484 in total) who accessed palliative care in Albania in the last 10 years (2014 to 2023). Information on patient age, breast cancer incidence, hospitalization and mortality rates, and breast cancer screening was collected. Descriptive statistics and t-test for unpaired samples to compare the means of age in the study period were used. The average age of patients gradually increased from 2014 to 2019, showing fluctuations due to the COVID-19 pandemic, and resumed an increasing trend in 2023. Breast cancer incidence remained stable at approximately 37 cases per 100,000 annually, with significant increases in hospitalization and screening rates over the study period. In conclusion, the gradual increase in the age of breast cancer patients seeking palliative care in Tirana, Albania during the past decade, coupled with slight decrease of mortality rates, stable incidence and increase of hospitalization might be indicators of success of related health policies in Albania, including better diagnostic and treatment strategies, improved treatment efficacy and disease management, ultimately increasing the resilience and adaptability of the healthcare system.